Hedgehog Suppresses Paclitaxel Sensitivity by Regulating Akt-Mediated Phosphorylation of Bax in EGFR Wild-Type Non-Small Cell Lung Cancer Cells - Tu, Yun-Chieh; Yeh, Wei-Chen; Yu, Hsin-Hsien; Lee, Yu-Cheng; Su, Bor-Chyuan (Frontiers in Pharmacology, 2022)
Non-small cell lung cancer (NSCLC) is one of the most common and deadly cancers worldwide. Among NSCLC patients, almost half have wild-type epidermal growth factor receptor (EGFR WT). The only therapeutic option for these EGFR WT NSCLC patients is chemotherapy, while NSCLC patients with EGFR mutations have more diverse therapeutic options, including EGFR tyrosine kinase inhibitors. Moreover, NSCLC patients with EGFR WT have worse chemotherapy response than EGFR mutant NSCLC patients. Thus, an urgent need exists for novel therapeutic strategies to improve chemotherapy response in EGFR WT NSCLC patients. Hedgehog signaling is known to be highly active in NSCLC; however, its potential role in chemoresistance is not fully understood. In the present study, we found that paclitaxel (PTX) treatment induces hedgehog signaling in EGFR WT NSCLC cells, and inhibition of hedgehog signaling with GDC-0449 (Vismodegib) increases sensitivity to PTX-stimulated apoptosis. Furthermore, GDC-0449 potentiates PTX-induced reactive oxygen species and mitochondrial dysfunction. In contrast, a hedgehog agonist, Hh-Ag1.5, attenuates PTX-induced apoptosis. Mechanistic experiments revealed that hedgehog induces phosphorylation of Akt at Ser473. Akt then phosphorylates Bax at Ser184, which can switch its activity from pro-apoptosis to anti-apoptosis. Taken together, our findings suggest that inhibition of hedgehog signaling might be a promising therapeutic strategy to improve PTX response in EGFR WT NSCLC.